(3EfTGA dJhdjI efUH GdJUOQ Ydi GdMaGXs - (3eMeO Hf GQGSe CHh GdeXaQ GdHQgGfj GdNhGQRejs
(3ChdgG (B:s
(3eeG dG jNai Ydi CQHGH GdCdHGH GdeJTHSjf ai GdcjGSI s
(3BNQgG (B:s
(3fbd GdTQY haQVg hChOY ajg TQMkG decfhf hYde GdMQa s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B20s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
Keywords: (3GdeLGejYs